IMPLEMENTASI NILAI-NILAI PANCASILA DAN TRANSFORMASI DIGITAL DALAM PENGUATAN KEDAULATAN EKONOMI INDONESIA - Gunawan Widjaja (NETIZEN: JOURNAL OF SOCIETY AND BUSSINESS, 2025)
This study discusses the implementation of Pancasila values and digital transformation as a strategy to strengthen Indonesia's economic sovereignty. Pancasila values such as social justice, mutual cooperation, unity, and independence are the philosophical foundation for building an inclusive, just, and sovereign economic system. Digital transformation offers significant opportunities to accelerate economic inclusion, expand market access, and enhance national competitiveness while upholding the nation's noble values. Through a literature review, this study reveals how the integration of Pancasila values in the utilisation of digital transformation contributes to creating an independent and sustainable Indonesian economy, while rejecting foreign economic dominance. The results of the study emphasise the importance of collaboration between the government, the private sector, and the community in building a fair and equitable digital ecosystem for the welfare of all Indonesians.